Urban transportation resilience in response to COVID-19: case of Polish cities - Kazak, Jan; Diakowska, Ewa; Pilawka, Tomasz; Sadowski, Artur; Wnętrzak, Małgorzata; Kamińska, Joanna (Bulletin of Geography. Socio-economic Series, 2024)
COVID-19 was a unique event that globally influenced socio-economic systems in many dimensions. One of them was transportation and mobility patterns, especially during lockdown introduced for the sake of public health. Although restrictions were rather universal within each country, cities were characterized by different mobility patterns. The aim of this study was to analyse changes in mobility patterns in response to COVID-19 and define similarities in urban transportation resilience. For this purpose COVID-19 – Community Mobility Reports were used. Results show that work-related mobility was the most influenced in the long term. Bigger cities needed more time to revert to pre-pandemic level. During the first month of lockdown mobility associated with workplaces as well as grocery and pharmacy presented similar decrease. The biggest decrease characterises mobility connected with retail and recreation. Although it met pre-pandemic patterns around the summer 2020, it required almost one more year to reduce fluctuations.